Village Fund Management Viewed from Accountability, Transparency and Community Participation (Study of Village Apparatus in Kasokandel District, Majalengka Regency) - Mochamad Febri Sayidil Umam; Tito Marta Sugema Dasuki; Ika Erika (Finance and Business Management Journal, 2023)
Village funds are foods that are prone to misuse if the village government is less responsible to the community. This study aims to determine the effect of accountability, transparency and community participation on the management of village funds in Kasokandel District, Majalengka Regency.This research method uses a survey method with an instrument test approach, descriptive and verification. The population of the research village in Kasokandel District, Majalengka Regency with a sample of 90 respondents. Analysis of the data used in this study is the classical assumption test, multiple linear regression, coefficient of determination and hypothesis testing. For partial test using t test and simultaneous test using F test.The results of this study indicate simultaneously or partially that accountability, transparency and community participation have a significant effect on the management of village funds in Kasokandel District, Majalengka Regency. This shows that the better the accountability, transparency and community participation, the better the management of village funds in Kasokandel District, Majalengka Regency. Village fund management aims to create good welfare in the village community. This study aims to determine the effect of accountability, transparency and community participation on the management of village funds in Kasokandel District, Majalengka Regency.